Clear‐cell chondrosarcomas: Fine‐needle aspiration cytology, radiological findings, and patient demographics of a rare entity. Issue 1 (12th August 2020) - Zhang, Yifan; Alagic, Zlatan; Tani, Edneia; Skorpil, Mikael; Tsagkozis, Panagiotis; Haglund, Felix
Abstract: Background: Clear‐cell chondrosarcomas (CCCSs) constitute a very rare subtype of chondrosarcoma. CCCS may radiologically mimic chondroblastoma, and given the difference in surgical approach, it is important to distinguish these two entities preoperatively. Design: Using the institutional digital records, we identified histologically verified CCCS between 1996 and 2013, where preoperative fine‐needle aspiration (FNA) cytology was available. Clinical characteristics were categorized and described, and FNAs were reviewed by a panel of senior cytopathologists. In addition, corresponding radiological imaging was reviewed by senior radiologists, and a literature review on CCCS and chondroblastoma was conducted. Results: A total of seven CCCS FNAs were identified from six patients. The cytomorphology showed low to intermediate cellular smears of clusters and single round or oval tumor cells. Tumor cells had rounded (sometimes binucleated) nuclei with limited pleomorphism and rich vacuolated cytoplasm. Chondroid background matrix was always found. While CCCS patients had a significantly higher age at diagnosis compared to chondroblastoma, no age cut‐off would distinctly separate the two. Conclusions: CCCS has distinguished cytomorphological features on FNA smears. CCCS should be considered as a possible differential diagnosis in adults (>25 years) with a radiological suspicion of chondroblastoma. Since radiology and patient age cannot conclusively distinguish CCCS from chondroblastoma, FNA may prove an important tool for correct preoperative diagnosis of CCCS.